A Research Review of “Dehli Ki Sham” in Postcolonial Context - Azam, Muhammad; Begum, Irshaad (sourcecoder, 2024)
Colonialism may be defined as to control an independent territory by other people without inhabitant will and wish. These people are called colonizers. They make reasonable arrangements for their residence and livelihood and occupy the resources of the local population by usurping their rights. The colonized are outnumbered but cannot challenge the power and resources of the colonizer. They willingly accept the rules laid down by the colonizer. Homi K Bhabha has a unique position and identity in terms of postcolonial studies. His recognition and uniqueness in literature and criticism is his postcolonial concepts, which he elaborated in his book "The Location of Culture" published in 1994. He has added a new chapter in literature and criticism by coining new terms like Mimicry, Hybridity, and Ambivalence. Ahmed Ali’s novel presents every aspect of Muslim life, their culture, daily life, anti-colonial rebellion and partiality and the uniqueness and hybridity of Muslim culture with other Indian cultures. The study shows how the colonizer changes colonized people culture and values for his nefarious purposes.